2012
DOI: 10.1620/tjem.226.161
|View full text |Cite
|
Sign up to set email alerts
|

Different Susceptibility to Insulin Resistance and Fatty Liver Depending on the Combination of TNF-.ALPHA. C-857T and Adiponectin G+276T Gene Polymorphisms in Japanese Subjects with Type 2 Diabetes

Abstract: The C-857T promoter polymorphism of TNF-α gene is associated with obese type 2 diabetes, while the adiponectin G+276T gene polymorphism in intron 2 may influence the fat accumulation in the liver. In this study, we examined effects of these polymorphisms on clinical markers of insulin resistance and fatty liver (a liver/spleen CT ratio < 0.9). These polymorphisms were determined in 342 Japanese subjects with type 2 diabetes. The liver/spleen CT ratio was lower in the subjects with the adiponectin +276G/G genot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…10 The À308G>A polymorphism was associated with the progression of impaired glucose tolerance to type 2 diabetes in Finns, 11 type 2 diabetes in Asians, 12,13 macrovascular complications in Scandinavians, 14 and renal disease in Poles and Chinese with diabetes. 15,16 In the Japanese population, the À857C>T polymorphism was associated with insulin resistance, 17 type 2 diabetes, 18 and carotid plaque formation in subjects with type 2 diabetes. 19 Therefore, these findings prompted us to test the hypothesis that the À238G>A (rs361525), À308G>A (rs1800629), and À857C>T (rs1799724) polymorphisms in the TNF gene are associated with DR in Caucasian Brazilians with type 2 diabetes.…”
mentioning
confidence: 99%
“…10 The À308G>A polymorphism was associated with the progression of impaired glucose tolerance to type 2 diabetes in Finns, 11 type 2 diabetes in Asians, 12,13 macrovascular complications in Scandinavians, 14 and renal disease in Poles and Chinese with diabetes. 15,16 In the Japanese population, the À857C>T polymorphism was associated with insulin resistance, 17 type 2 diabetes, 18 and carotid plaque formation in subjects with type 2 diabetes. 19 Therefore, these findings prompted us to test the hypothesis that the À238G>A (rs361525), À308G>A (rs1800629), and À857C>T (rs1799724) polymorphisms in the TNF gene are associated with DR in Caucasian Brazilians with type 2 diabetes.…”
mentioning
confidence: 99%
“…In Japanese population, -857C>T (rs1799724) polymorphism is associated with insulin resistance, T2DM, and carotid plaque formation in T2DM patients (Kamizono et al 2000;Buraczynska et al 2004;Wang et al 2005;Yamashina et al 2007;Ohara et al 2012). However, Sesti et al (2015) found an independent association of the 308G>A polymorphism in the TNFα gene with proliferative diabetic retinopathy PDR in Caucasian Brazilians with T2DM, not -857C>T (rs1799724) polymorphism.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, another recent meta-analyses has reported that TNF-α -238G>A and -308G>A polymorphisms were not associated with type 2 diabetes mellitus; however, -308G>A polymorphism was positively associated with type 1 diabetes (Feng et al, 2009a;Feng et al, 2009b;Feng et al, 2011). TNF-α -857C>T polymorphism is also associated with obese type 2 diabetes (Kamizono et al 2000) and insulin resistance in Japanese diabetic subjects with adiponectin +276GG genotype (Ohara et al, 2012). The study of Ohara et al has shown interaction of TNF-α and adiponectin genes with insulin resistance and fatty liver (Ohara et al, 2012).…”
Section: The Polymorphisms Of the Tnf-α Genementioning
confidence: 95%
“…TNF-α -857C>T polymorphism is also associated with obese type 2 diabetes (Kamizono et al 2000) and insulin resistance in Japanese diabetic subjects with adiponectin +276GG genotype (Ohara et al, 2012). The study of Ohara et al has shown interaction of TNF-α and adiponectin genes with insulin resistance and fatty liver (Ohara et al, 2012).…”
Section: The Polymorphisms Of the Tnf-α Genementioning
confidence: 99%